Toxic Leaching of Heavy Metals in Copper Catalyst Residue - Zhang, L.; Ying, T.; Yang, H.Y.; Chang, Z.X.; Li, D.L. (Asian Journal of Chemistry, 2012)
The authors compared identification standard for hazardous wastes-extraction procedure toxicity of China and Japan and toxicity characteristic leaching procedure of United States to evaluate which is better to identify toxicity characteristic of typical copper catalyst of China. They also studied leaching characteristic of metals in copper catalyst under different pH values. The results showed that pH was a major controlling factor in metal leachability. The metals exhibited a marked increase in leachability at low, while relatively low leachability of these metals were observed at neutral conditions.